THE PSYCHOLOGICAL AND PEDAGOGICAL MODEL FOR DEVELOPING EMOTIONAL INTELLIGENCE IN PROFESSIONAL EDUCATION - Tursunova Ozoda Fakhriddinovna (Bright Mind Publishing, 2025)
The article explores the psychological and pedagogical foundations of developing emotional intelligence within the context of professional education. It emphasizes the growing importance of emotional competence as a key factor in students’ professional and personal development in the modern educational environment. The study presents a structural-functional model that integrates cognitive, emotional, motivational, and behavioral components aimed at enhancing self-awareness, empathy, emotional regulation, and communication skills. The proposed model is based on humanistic and competence-based approaches, combining interactive methods, reflective practices, and digital learning tools. The results demonstrate that the development of emotional intelligence contributes to improving students’ social adaptation, teamwork, and professional resilience, thus ensuring higher efficiency and psychological well-being in professional education.
Keywords: emotional intelligence, professional education, psychological and pedagogical model, empathy, self-regulation, communication competence, emotional competence, reflective learning.